In vivo assessment of buparvaquone resistant Theileria annulata populations: genetic structure, transmission dynamics, drug susceptibility and pharmacokinetics - Selin Hacilarlioglu; Huseyin Bilgin Bilgic; Cengiz Gokbulut; Serkan Bakirci; Ayca Aksulu; Brian Shiels; Andrew Tait; Onur Kose; Metin Pekagirbas; William Weir; Dilek Aksit; Tulin Karagenc (PLoS ONE, 2025)
Tropical theileriosis, caused by the protozoan parasite Theileria annulata and transmitted by several species of ixodid ticks of the genus Hyalomma, is an economically important disease of bovines. Concerningly, studies conducted in recent years have shown an increase in the rate of failure when using the primary drug of treatment, buparvaquone (BPQ), particularly in infection caused by T. annulata populations bearing V135A and P253S mutations on the Cytochrome b (Cyto b) gene of the parasite mitochondrial genome. The aim of this study was to demonstrate the relationship between BPQ-resistance and V135A and P253S mutations utilising an in vivo experimental set-up and to assess the tick transmissibility of drug-resistant populations. Additionally, the pharmacokinetics of BPQ in healthy and infected calves were compared to evaluate any relationship between plasma drug concentration and treatment failure. The study results demonstrated that, despite four consecutive BPQ treatments, animals infected with the resistant isolates exhibited more severe clinical signs, including longer periods of pyrexia, longer periods of schizont and piroplasm parasitemia, and the death of one animal. In addition, 3-(4,5-dimethylthiazol--yl)-2,5-diphenyltetrazolium bromide (MTT) analyses showed that all cell lines derived from animals infected with the mutant genotypes exhibited resistance to high BPQ concentrations. Unexpectedly, despite substantial calf-to-calf variation during the experiment, the genetic structure of the parasite population remained largely unchanged and no strong evidence for a major genotypic shift was detected. Plasma BPQ levels were similar in all groups tested. There was no association between plasma concentrations of BPQ and parasitological or clinical response to treatment. Live parasitaemia was observed even at high plasma BPQ levels in animals infected with resistant isolates. Significantly, drug resistant parasite populations harbouring either V135A or P253S mutations was transferred between the host and vector ticks, indicating the potential for resistant parasites to be transmitted from cattle in the field, thereby facilitating their maintenance in natural populations.